Generating socially responsible events at ski resorts. (October 2020) - Taheri, Babak; Thompson, Jamie
Highlights: Uses mixed-methods to understand socially responsible sponsorship-linked sport events. Using a consumer questionnaire, evaluates relationships among CSR, OSE, involvement and satisfaction. Probes local resort workers' perceptions of ski resorts and their desires for the future of event management. Contributes to the CSR literature. Abstract: This study examines how ski resorts can manage events that are sustainable, while also balancing the needs of consumers and local workers. Using a mixed-method approach, quantitative results (from 710 ski tourists) highlight the influence of community-centric Corporate Social Responsibility (CSR) and Orientation towards Sporting Events (OSE) on the involvement and satisfaction of visitors in sponsorship-linked events within Iranian ski resorts. Qualitative results (from 38 local resort workers) suggest local resort workers desire community engagement, personal well-being, and rejuvenation. The implications this has for hospitality development are discussed alongside the theoretical implications for future research exploring community-based CSR and Event Social Responsibility (ESR).